2018
DOI: 10.1039/c7ra12297g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of curcuminoid microemulsions fromCurcuma longaL. to enhance inhibition effects on growth of colon cancer cells HT-29

Abstract: The objectives of this study were to extract curcuminoids from a vital medicinal plant Curcuma longa L. and prepare the curcuminoid extract and microemulsion for studying the inhibition mechanism of HT-29 colon cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Fortunately, with the help of the ζ-potential value, the colloidal stability of the droplets can be demonstrated. The literature shows that because of electrostatic repulsion between nanoparticles, the highly stable μE droplets have a ζ-potential value of >30 or <−30 mV. ,,, In this research, the ζ-potential of the EZM-free μE was −32.5 ± 1.4 mV, indicating the high stability of the μE. In contrast, a slightly higher negative ζ-potential (−38.7 ± 1.9 mV) of the EZM-loaded μE indicates its high stability.…”
Section: Resultsmentioning
confidence: 53%
“…Fortunately, with the help of the ζ-potential value, the colloidal stability of the droplets can be demonstrated. The literature shows that because of electrostatic repulsion between nanoparticles, the highly stable μE droplets have a ζ-potential value of >30 or <−30 mV. ,,, In this research, the ζ-potential of the EZM-free μE was −32.5 ± 1.4 mV, indicating the high stability of the μE. In contrast, a slightly higher negative ζ-potential (−38.7 ± 1.9 mV) of the EZM-loaded μE indicates its high stability.…”
Section: Resultsmentioning
confidence: 53%
“…Sharma et al reported an EE of 69.98 ± 0.21 to 83.32 ± 0.15% for curcumin-loaded Pluronic F-127 microemulsions [ 83 ]. Chen et al prepared curcuminoid microemulsions consisting of soybean oil, Tween 80, ethanol, and water with an EE of 85.7% [ 84 ]. Based on this study, this high EE percentage may be due to interactions between curcumin and microemulsions, which can result in a more rigid microemulsion membrane and affect curcumin release.…”
Section: Resultsmentioning
confidence: 99%
“…Annexin V/PI assay can distinguish apoptotic and necrotic cells using both Annexin V-fluorescein isothiocyanate (FITC) and propidium iodide (PI) stains, established on translocation of phosphatidylserine (PS) from the inner plasma membrane into outer cell surface in apoptotic cells where it can particularly bind with a fluorescent Annexin V -FITC, also PI can distinguish permeabilized plasma membrane of necrotic cells. Thus the percentages of apoptosis/necrosis cells in untreated SKOV3 cells and the treated SKOV3 ovarian cancer cells that were previously treated with an IC 50 concentration of SnO 2 NPs and FA-SnO 2 NPs for 24 h, was assessed by an Annexin V-FITC detection kit I (BD Biosciences) as previously mentioned [38,39]. Briefly,…”
Section: Lactate Dehydrogenase Leakage Test (Ldh)mentioning
confidence: 99%